2022
DOI: 10.3390/foods11050732
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Muscle Protein Changes as a Tool for Monitoring Sahraoui Dromedary Meat Quality Characteristics

Abstract: The effects of slaughter age (2 vs. 9 years) and postmortem time (6, 8, 10, 12, 24, 48 and 72 h) on the meat quality and protein changes of the longissimus lumborum muscles of the Algerian Sahraoui dromedary were investigated. Muscles of young dromedaries evidenced a slower acidification process and a significantly higher myofibrillar fragmentation index throughout the postmortem time. The SDS-PAGE of sarcoplasmic and myofibrillar proteins revealed that meat from young dromedaries was characterized by the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Meat with shorter sarcomeres is tougher compared to that with longer sarcomeres (Haeger et al, 2020 ). According to Smili et al ( 2022 ), the increase in myofibrillar fragmentation is an indication of the extent of tenderisation that has occurred. Hope-Jones and Strydom ( 2021 ) reported a relationship between MFL with sensory tenderness and shear force measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Meat with shorter sarcomeres is tougher compared to that with longer sarcomeres (Haeger et al, 2020 ). According to Smili et al ( 2022 ), the increase in myofibrillar fragmentation is an indication of the extent of tenderisation that has occurred. Hope-Jones and Strydom ( 2021 ) reported a relationship between MFL with sensory tenderness and shear force measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This index is a very useful indicator of meat tenderness (shear–force and sensory panel tenderness). Smili et al (2022) reported that MFI of Algerian Sahraoui dromedary meat was significantly affected by both slaughter age and post – mortem period. The same authors confirmed that the 30–kDa band is a proteolytic product of Troponin–T in camel Longissimus lumborum muscles.…”
Section: Organoleptic Properties Of Camel Meatmentioning
confidence: 99%
“…This index is a very useful indicator of meat tenderness. Smili et al (2022) reported that MFI of Algerian Sahraoui dromedary meat was significantly affected by both slaughter age and post mortem period. The same authors confirmed that the 30-kDa band is a proteolytic product of Troponin-T in camel longissimus lumborum muscles.…”
Section: Tendernessmentioning
confidence: 99%